2005
DOI: 10.1097/01.md.0000158792.24888.d2
|View full text |Cite
|
Sign up to set email alerts
|

Brain Magnetic Resonance Imaging in Patients With Cowden Syndrome

Abstract: Cowden syndrome (CS) is a rare autosomal dominant genodermatosis, characterized by multiple hamartomas, particularly of the skin, associated with high frequencies of breast, thyroid, and genitourinary malignancies. Although Lhermitte-Duclos disease (LDD) or dysplastic gangliocytoma of the cerebellum, a slowly progressive unilateral tumor, is a major criterion of CS, its frequency in patients with CS is unknown. Other cerebral abnormalities, especially meningioma and vascular malformations, have also been descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
79
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(85 citation statements)
references
References 37 publications
6
79
0
Order By: Relevance
“…23 High frequency of vascular malformations was noted in a study of 20 patients with CS, where 5 patients had venous angiomas (3 associated with Lhermitte-Duclos disease [LDD]) and 2 patients had cavernous angi- omas (1 associated with LDD) with a significant proportion related to LDD. 14 No vascular anomalies were found in our 7 patients, but this probably is an underestimate because none of our patients received contrast material. More recently, congenitally enlarged VR spaces have been described in a case of BRRS.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…23 High frequency of vascular malformations was noted in a study of 20 patients with CS, where 5 patients had venous angiomas (3 associated with Lhermitte-Duclos disease [LDD]) and 2 patients had cavernous angi- omas (1 associated with LDD) with a significant proportion related to LDD. 14 No vascular anomalies were found in our 7 patients, but this probably is an underestimate because none of our patients received contrast material. More recently, congenitally enlarged VR spaces have been described in a case of BRRS.…”
Section: Discussionmentioning
confidence: 82%
“…19 Published case reports have described rare cases of meningiomas, frontal vascular hamartoma, intracranial lipomatous hamartoma, and malignant intracranial human chorionic gonadotropin-secreting tumor in patients with BRRS. 14,20 The PTEN/PI3K pathway governs normal vascular development and tumor angiogenesis. 21 High-flow vascular malformations, 1 including dural AVM, 10 hemangiomata, and vertebral angiomas, 22 may exist in patients with BRRS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our best knowledge, there is no known link between LDD or PTEN mutations and any of these conditions. However, PTEN mutations are associated with a high rate of vascular malformations [37] and several studies demonstrated cavernous and venous angiomas [22] as well as other developmental vascular abnormalities in LDD [2,27,41]. An association of this mutation with LDD may explain striking hypervascularisation of gangliocytomas observed in one large study [1], and possible contribution to the widespread presence of telangiectasias in our patient.…”
Section: A B a B Discussionmentioning
confidence: 76%
“…To our knowledge, such brain MRI imaging has not been described previously in Cowden syndrome. 9 Apart from regulating cell growth, the PTEN gene also plays a role in cell migration. It interacts with focal adhesion kinase, which results in the inhibition of cell migration and spread.…”
Section: Discussionmentioning
confidence: 99%